2020
DOI: 10.1590/0034-7167-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students: medication use, psychoactive substances and health conditions

Abstract: Objective: to assess the use of nonprescription psychoactive medications and their associations with psychoactive substance use and health aspects among nursing students. Method: a cross-sectional study conducted with 182 students at a nursing school in the city of Vale do Ribeira, Brazil. Sociodemographic information, screening for alcohol, tobacco and other drug use, information on physical and mental health and physical activity practices were assessed. Results: more than half of the students (79.2%) used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
9
Order By: Relevance
“…On the other hand, an investigation identified that nursing students preferred to consult people close to them to seek specialized help for symptoms of mental disorders (17) . The belief in spontaneous resolution of the problem or the search for unskilled help increases the risk of underestimating important symptoms and worsening of the condition (17)(18)(19) . With regards to other psychoactive substance consumption, there was a prevalence of alcohol, followed by nicotine and marijuana.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, an investigation identified that nursing students preferred to consult people close to them to seek specialized help for symptoms of mental disorders (17) . The belief in spontaneous resolution of the problem or the search for unskilled help increases the risk of underestimating important symptoms and worsening of the condition (17)(18)(19) . With regards to other psychoactive substance consumption, there was a prevalence of alcohol, followed by nicotine and marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation presented in the studies, the literature has highlighted the prevalence of high alcohol, nicotine and marijuana consumption among undergraduate students, but the socio-cultural, climatic or economic differences may be related to this variation (17,(22)(23) . An investigation carried out with 182 Brazilian nursing students identified that 56.6% had used alcohol in the last 30 days preceding the research, 11% were smokers, 54.5% had a mean level of nicotine dependence and 10.4% had already tried some illicit drug (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo os 25 artigos selecionados, foi possível identificar que 10 estudos abordam a prevalência de estresse, ansiedade e/ou depressão entre alunos de graduação (Bertani et al, 2020;Costa et al, 2020;Cukrowicz et al, 2011;Granados Cosme et al, 2020;Ibrahim & Abdelreheem, 2015;Martínez-Martínez et al, 2016;Mohammad et al, 2020;Moreira et al, 2015;Pokhrel et al, 2020;Ramón-Arbués et al, 2020), sendo que 2 associam a relação desses transtornos com tendências suicidas (Cukrowicz et al, 2011;Granados Cosme et al, 2020). Além disso, 15 artigos discutem sobre o consumo de psicofármacos entre estudantes de universidades (Betancourt et al, 2013;Boclin et al, 2020;Câmara et al, 2011;Davis et al, 2019;Demenech et al, 2020;Hernandez & Nelson, 2010;Hildt et al, 2015;Lecat et al, 2020;Martins & Ghandour, 2017;Oliveira et al, 2019;Papazisis et al, 2017;Parks et al, 2017;Sousa et al, 2020;Stone & Merlo, 2010;Zullig & Divin, 2012), dos quais 3 estudos investigaram sua influência em comportamentos e pensamentos suicidas (Davis et al, 2019;Lecat et al, 2020;Zullig & Divin, 2012). (Tabela 1).…”
Section: Etapas De Seleçãounclassified
“…Um estudo conduzido na Universidade Federal do Rio Grande (FURG) em 2015 demonstrou que o uso não médico de psicofármacos por estudantes de graduação é maior que quando comparada a população brasileira (25,2% vs. 8,4%) (Demenech et al, 2020). É sugerido que a maior facilidade de acesso a drogas prescritas em comparação a drogas ilícitas, na maioria das vezes adquiridas por amigos, familiares ou até pela "internet", o fato de serem mais aceitas socialmente (Hernandez & Nelson, 2010;Sousa et al, 2020), o desconhecimento sobre os possíveis riscos (efeitos colaterais, dependência, tolerância e abstinência) e o engano de que o uso de medicações prescritas é menos danoso que substâncias ilícitas (National Institute on Drug Abuse (NIDA), 2018; Sousa et al, 2020) sejam os principais motivos da crescente prevalência dessa prática nas universidades (Parks et al, 2017;Sousa et al, 2020).…”
Section: Introductionunclassified